Improving the Accessibility of Frontline Services : For Equitable Care Amidst Rapid Growth and Urbanization (World Bank, Washington, DC, 2019)
In rapidly growing urban centers, most residents are near health services. Nonetheless, a range of social and financial constraints can deter individuals and families from seeking care, preventing timely diagnosis of chronic and infectious conditions. Creative and sensitive outreach strategies, new approaches to proactive case finding, and progressive payment models are needed to surmount social and economic cleavages that drive persistent inequities, and to improve the accessibility of timely diagnosis and high-quality care in urban and peri-urban communities.